THE EFFECT OF BAMBOOZLE GAME ON VOCABULARY MASTERY OF THE FIFTH GRADE STUDENTS OF SDN 3 KARANGEBENDO IN THE ACADEMIC YEAR 2023/2024 - Halim, Abdul; Khoirotun Nisa; Wiwin Indiarti (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
English learning by games becomes a phenomenon. In this research game applied on teaching vocabulary mastery at SDN 3 Karangbendo. This research aims to investigate whether there is any effect of Bamboozle game for teaching vocabulary mastery in fifth grade students of SDN 3 Karangbendo. This research is quantitative research with the experimental research design. There are 14 respondents of fifth grade students in SDN 3 Karangbendo. Purposive sampling technique is used to choose the respondents. Multiple choice tests were chosen for the data collecting method that consist 20 questions of common nouns and verbs. For the data analysis used t-test formula. The researcher found that there is enhancement on the post-test. The mean score was 42.85 in the pre-test and 60.71 in the post-test. The result of t-test is higher than t-table (20.679 > 2.160). It can be concluded that there is significant effect of Bamboozle game for teaching vocabulary mastery in the fifth grade students of SDN 3 Karangbendo.